The Impact of FDI on the Structure of the Kosovo Economy - Kida, Nakije Miftar (European Journal of Economics and Business Studies, 2017)
This study has addressed the impact of domestic investment and FDI net flow from the services sector on economic growth for a period of 10 years. The data are taken from CBK, in annual periods, using the technique of Pearson correlation and multiple OLS regression, conducted with the statistical program SPSS 21.0. FDI attraction by the services sector is found to be greater than by the other sectors. This becomes more evident by findings from econometric analysis, where the services sector has a strong impact on economic growth in the country. Meanwhile, the "crowding out" effect has happened, indicating that local investment (local firms) has a modest level of technical and managerial changes, since increasing effect is estimated to be negative. According to this study, the economy of Kosovo has grown with an average rate of 4 percent for 16 years and the biggest contributor is the services sector with 56 percent of GDP, which includes financial services, insurance companies, construction, telecommunications, real estate, trade etc. This pace still continues to be a model of economic growth in Kosovo and continues to be supported by certain economic policies, while other sectors lag behind. This result clearly shows that, although the level of FDI inflows in Kosovo is low, the sector specification shows positive trend of incoming flows in the services sector. This is due to dominance in market of the financial sector and that of insurance with foreign capital as the only financing source of the local businesses.
Keywords: FDI, GDP growth rate, Domestic investment, Services sectors, Kosovo.